Development of New Adsorbent Based on Coconut Waste for Removal of Lead from Aqueous Solution - ABDUL RAHIM, ABDUL RAHMAN (2020)
Activated carbon (AC) is one of commercialized adsorbent that were conventionally utilized for the application of abating heavy metal pollutions in the environment. However, it can be financially burdening to use AC as it is expensive due to its complex manufacturing process and its low regenerative value. As an alternative, agriculture waste (AWs) have been explored for its application as char adsorbent precursor to remove lead. Its application is economically attractive as the waste is abundant, can be obtained at minimal cost and would only require minimal processing before can be utilized as char adsorbent. In this research study, desiccated coconut waste (DCW), were utilized as char adsorbent precursor for removal of lead, Pb(II). The waste were processed and were thermally and chemically treated.